THE CONTRIBUTION OF PESANTREN’S MEANING SYMBOLS AND THEIR EFFECTS ON TRANSLATION OF ARABIC TEXT - Ammar, Adzfar; Munip, Abdul; Musthofa, Tulus; B. Sapar, Ahmad Arifin; Setiyawan, Agung (Arabi : Journal of Arabic Studies, 2022)
This article aims to explain the contribution of the gandul pesantren’s meaning symbols and reveal the problems in translating Arabic sentences. The method of data collection is done through observation and documentation from several sources related to the meaning of the Islamic boarding school and translation with the main data source in the form of a book entitled "Fathul Qarib Paling Lengkap" by M. Hamim HR. and Huda Nailul which is then analyzed and the results are described qualitatively. The results of the study show that: (1) There are 4 contributions of the symbol of the Islamic boarding school meaning in translating Arabic texts, namely: the translation process becomes more effective and efficient, helps to know the position of a word in a sentence, helps to read Arabic texts and helps understand the message referred to from an Arabic sentence. (2) The meaning of the Islamic boarding school which has several terms symbolized by certain symbols used to explain the position of words in Arabic sentences has problems in translating them into Indonesian because not all terms can be directly translated so that some of them are not included (omitted) in translation.